1726 Parents' Satisfaction with care During the Birth of their Very Preterm Baby: A Qualitative Study. (October 2012) - Sawyer, A; Rabe, H; Abbott, J; Ayers, S; Gyte, G; Duley, L
Abstract : Background and Aims: Satisfaction with childbirth is an important indicator of quality of care and is related to the health and well-being of the mother and her baby. Parents' experiences of care during preterm birth has received little attention. Therefore the aim of this study was to explore parents' experiences and satisfaction with care during the birth of their preterm baby and to identify aspects of care that they perceived as important. Methods: Parents were eligible for the study if they had a baby born less than 32 weeks gestation and spoke English well. Semi-structured interviews were carried out with 32 mothers and 7 fathers about their experiences of care during the birth. Results: Results showed the majority of parents were very satisfied with the care during the birth. Thematic analysis identified four key determinants of satisfaction: staff professionalism, which included information and explanation, staff being calm in a crisis, staff appearing confident and in control, staff not responding to the patient; staff empathy, which included caring and emotional support, encouragement and reassurance; birth environment; and involvement of father. Conclusions: Although these dimensions are generally consistent with previous research on birth satisfaction a number of unique factors to preterm birth were also identified. Improvements in care during preterm births should focus on providing information and explanations to parents, offering caring and emotional support, and involving fathers during the birth. Acknowledgement: Funding Body - National Institute of Health Research (RPPG060910107).